Climate Change Impacts on Agricultural Infrastructure and Resources: Insights from Communal Land Farming Systems - Bonginkosi E. Mthembu; Thobani Cele; Xolile Mkhize (Land, 2025)
Climate change significantly impacts agricultural infrastructure, particularly in communal land farming systems, where socio-economic vulnerabilities intersect with environmental stressors. This study examined the effects of extreme weather events (floods, droughts, strong winds, frost, and hail) on various agricultural infrastructures—including bridges, arable land, soil erosion control structures, dipping tanks, roads, and fences—using an ordered probit model. A survey was conducted using structured questionnaires between August and September 2023, collecting data from communal farmers (n = 60) in oKhahlamba Municipality, Bergville. Key results from respondents showed that roads (87%), bridges (85%), and both arable land and erosion structures were reported as highly affected by extreme weather events, especially flooding and frost. Gender, the type of farmer, access to climate information, and exposure to extreme weather significantly influenced perceived impact severity. The ordered probit regression model results reveal that drought (p = 0.05), floods (p = 0.1), strong winds (p = 0.05), and frost (p = 0.1) significantly influence the perceived impacts on infrastructure. Extreme weather events, including flooding (p = 0.012) and frost (p = 0.018), are critical drivers of infrastructure damage, particularly for smallholder farmers. Cumulative impacts—such as repeated infrastructure failure, access disruptions, and increased repair burdens—compound over time, further weakening resilience. The results underscore the urgent need for investments in flood-resilient roads and bridges, improved erosion control systems, and livestock water infrastructure. Support should also include gender-sensitive adaptation strategies, education on climate risk, and dedicated financial mechanisms for smallholder farmers. These findings contribute to global policy discourses on climate adaptation, aligning with SDGs 2 (Zero Hunger), 9 (Industry, Innovation, and Infrastructure), and 13 (Climate Action), and offer actionable insights for building infrastructure resilience in vulnerable rural contexts.